Pendeteksian Financial Statement Fraud Menggunakan Fraud Hexagon Theory Pada Perusahaan Telekomunikasi - Diana Sari, Ni Luh Ayu Linda; Ariyanto, Dodik; Paramadina, Aulia Ayu (E-Jurnal Akuntansi; Vol 34 No 2 (2024)DO - 10.24843/EJA.2024.v34.i02.p03, 2024)
This research aims to detect financial statement fraud using fraud hexagon theory. Testing was carried out at telecommunications companies listed on the Indonesia Stock Exchange during 2019-2021 during the Covid-19 pandemic. Sample selection was carried out using a purposive sampling technique. Data analysis uses panel data regression. Based on the results of the analysis, it shows that the variables financial target, change in auditor, frequent number of CEO's picture, and state-owned enterprises have a positive effect on financial statement fraud. Meanwhile, the variables financial stability, nature of industry, ineffective monitoring, and change of auditor have no effect on financial statement fraud. The implications of this research are for parties who need information regarding the opportunities for financial statement fraud to arise in telecommunications companies during the Covid-19 pandemic by considering the influencing factors. Keywords: Fraud Hexagon Theory; Financial Statement Fraud; Telecommunication Companies.